THE ROLE OF PUBLIC ADMINISTRATION IN ENSURING THE ECONOMIC SECURITY OF THE STATE BY OVERCOMING BARRIERS TO INNOVATIVE DEVELOPMENT OF ENTERPRISES - VERBYTSKA, Halyna (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The purpose of the article is to analyse the existing barriers to innovation development in Ukraine and to formulate public administration mechanisms to support and develop innovations in order to ensure the economic security of the State. The study uses the scientific methods of induction and deduction, analysis and synthesis, and comparison. The results of the study showed that Ukraine's industry needs a radical modernisation to intensify innovation. Raw materials and semi-finished products account for more than three quarters of domestic exports. This makes the economy vulnerable to fluctuations in global commodity prices and reduces its competitiveness. Reducing dependence on raw material exports and increasing the share of high value-added products are critical for economic stability and growth of the domestic economy. It is proved that investing in the latest technologies, infrastructure development and support for research and development are key steps to ensure the competitiveness and economic security of the state. The barriers to innovative development of enterprises are identified. They include constant shelling, expansion of the combat zone, frequent power outages, lack of own financial resources, lack of tax benefits for domestic innovative enterprises, weak ties between industry and leading research institutions and higher education institutions, as well as poor investment climate of the state. The article proposes a set of measures to overcome these barriers, including the development of effective public administration mechanisms, stimulation of investments in technological innovations and strengthening of cooperation between public administration, industry and research institutions. Implementation of these measures will allow Ukraine to overcome the existing barriers, win the war, rebuild its economy and become a successful country.
Keywords: public control; enterprise; economic security; harvest